Intellectual Property Protection and U.S. Foreign Direct Investment - Lee, Jeong-Yeon; Mansfield, Edwin (The Review of Economics and Statistics, 1996)
This is one of the first empirical studies of the relationship between a developing country's system of intellectual property protection and the volume and composition of U.S. foreign direct investment in that country. Based on data obtained from almost one hundred U.S. firms regarding their perceptions of how weak or strong such protection is in various countries, the authors' results are consistent with the view that a country's system of intellectual property protection influences the volume and composition of U.S. foreign direct investment. Copyright 1996 by MIT Press.